PERFORMANCE DIFFERENCE VIEWED FROM QUALITY OF LEADERSHIP, EMOTIONAL INTELLIGENCE AND WORKING MOTIVATION OF TEACHERS IN SMA AND SMK BATIK - Ambang Wibana; Istiatin .; Bambang Mursito (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
The purpose of the research are to analyze: 1) Differences in the performance teachers of SMA and SMK Batik Surakarta in terms of leadership quality; 2) Differences in the performance teachers of SMA and SMK Batik Surakarta in terms of emotional intelligence; 3) Differences in the performance teachers of SMA and SMK Batik Surakarta in terms of work motivation. The population of research 181 teachers in SMA and SMK Batik Surakarta. The sample was 100 teachers. Data analysis techniques using different test analysis independent sample t-test. The result of research showed that; 1) leadership  quality variable  has   t-count value of 2,152 and sig value 0,034 < 0,05, meaning that there are differences in the performance teachers of SMA and SMK Batik Surakarta; 2) emotional intelligence variable obtained value of t count 2,120 and sig value 0,036 < 0,05, meaning that there are differences in the performance teachers of SMA and SMK Batik Surakarta; 3) work motivation variables obtained t value of 2.995 and have a sig value of 0.004 < 0.05, meaning that there are differences in the performance teachers of SMA and SMK Batik Surakarta in terms of work motivation